Targeting mTOR with MLN0128 Overcomes Rapamycin and Chemoresistant Primary Effusion Lymphoma - Carolina Caro-Vegas (American Society for Microbiology, 2019)
ABSTRACT Primary effusion lymphoma (PEL) is caused by Kaposi’s sarcoma-associated herpesvirus (KSHV). PEL has a highly active mTOR pathway, which makes mTOR a potential therapeutic target. MLN0128 is an ATP-competitive inhibitor of mTOR that has entered clinical trials for solid tumors. Our results demonstrated that MLN0128 has a greater effect on inhibiting proliferation than the allosteric mTOR inhibitor rapamycin. MLN0128 has ∼30 nM 50% inhibitory concentration (IC50) across several PEL cell lines, including PEL that is resistant to conventional chemotherapy. MLN0128 induced apoptosis in PEL, whereas rapamycin induced G1 arrest, consistent with a different mechanism of action. MLN0128 inhibited phosphorylation of mTOR complex 1 and 2 targets, while rapamycin only partially inhibited mTOR complex 1 targets. PEL xenograft mouse models treated with MLN0128 showed reduced effusion volumes in comparison to the vehicle-treated group. Rapamycin-resistant (RR) clones with an IC50 for rapamycin 10 times higher than the parental IC50 emerged consistently after rapamycin exposure as a result of transcriptional adaptation. MLN0128 was nevertheless capable of inducing apoptosis in these RR clones. Our results suggest that MLN0128 might offer a new approach to the treatment of chemotherapy-resistant PEL. IMPORTANCE Primary effusion lymphoma (PEL) is an aggressive and incurable malignancy, which is usually characterized by lymphomatous effusions in body cavities without tumor masses. PEL has no established treatment and a poor prognosis, with a median survival time shorter than 6 months. PEL usually develops in the context of immunosuppression, such as HIV infection or post-organ transplantation. The optimal treatment for PEL has not been established, as PEL is generally resistant to traditional chemotherapy. The molecular drivers for PEL are still unknown; however, PEL displays a constitutively active mammalian target of rapamycin (mTOR) pathway, which is critical for metabolic and cell survival mechanisms. Therefore, the evaluation of novel agents targeting the mTOR pathway could be clinically relevant for the treatment of PEL.